A Guidebook of Group Guidance Services with Role Play ContainsWelas Asih to Prevent Verbal Bullying - Rahmawati, Septia; Setiyowati, Arbin Janu; Eva, Nur (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The act of verbal bullying is a feeling harsh, the impacts can be generated such are problem of social, psychological and academic problems, from those impacts it is necessary to have a comprehensive prevention effort. This research and development seek to construct a group counselling guideline book using role-play techniques with welas asih to prevent verbal bullying in Junior High School (JHS). This study uses the ADDIE model research and development approach (Analysis, Design, Development, Implementation and Evaluation). Based on the results of the analysis of research data, validation of guidance and counselling material experts, validation of cultural experts, validation of learning media experts, and potential product users as well as effectiveness tests, it can be concluded that the group counselling guideline book use role play technique with welas asih to prevent verbal bullying in Junior High School (JHS) is in the very good category according to the aspects of product acceptability (accuracy, usability, convenience, and attractiveness). Based on the results of limited field tests, it shows that a group counselling guideline book using role-play techniques with welas asih is effective in preventing acts of verbal bullying in Junior High School (JHS).